Vivaxin genes encode highly immunogenic, non-variant antigens on the Trypanosoma vivax cell-surface - Romero-Ramirez, Alessandra; Casas-Sánchez, Aitor; Autheman, Delphine; Duffy, Craig W.; Brandt, Cordelia; Clare, Simon; Harcourt, Katherine; André, Marcos Rogério [UNESP]; Neto, Kayo José Garcia de Almeida Castilho [UNESP]; Teixeira, Marta M. G.; Machado, Rosangela Zacharias [UNESP]; Coombes, Janine; et al. (Public Library of Science (PLoS), 2022)
Trypanosoma vivax is a unicellular hemoparasite, and a principal cause of animal African trypanosomiasis (AAT), a vector-borne and potentially fatal livestock disease across sub-Saharan Africa. Previously, we identified diverse T. vivax-specific genes that were predicted to encode cell surface proteins. Here, we examine the immune responses of naturally and experimentally infected hosts to these unique parasite antigens, to identify immunogens that could become vaccine candidates. Immunoprofiling of host serum shows that one particular family (Fam34) elicits a consistent IgG antibody response. This gene family, which we now call Vivaxin, encodes at least 124 transmembrane glycoproteins that display quite distinct expression profiles and patterns of genetic variation. We focused on one gene (viv-β8) that encodes one particularly immunogenic vivaxin protein and which is highly expressed during infections but displays minimal polymorphism across the parasite population. Vaccination of mice with VIVβ8 adjuvanted with Quil-A elicits a strong, balanced immune response and delays parasite proliferation in some animals but, ultimately, it does not prevent disease. Although VIVβ8 is localized across the cell body and flagellar membrane, live immunostaining indicates that VIVβ8 is largely inaccessible to antibody in vivo. However, our phylogenetic analysis shows that vivaxin includes other antigens shown recently to induce immunity against T. vivax. Thus, the introduction of vivaxin represents an important advance in our understanding of the T. vivax cell surface. Besides being a source of proven and promising vaccine antigens, the gene family is clearly an important component of the parasite glycocalyx, with potential to influence host-parasite interactions.